Physical and morphological characteristics of the first three jets of pêga jackasses sperm-rich fraction - Carvalho, L. E.; Silva Filho, J. M.; Palhares, M. S.; Sales, A. L.R.; Gonczarowska, A. T.; Oliveira, H. N. [UNESP]; Resende, M.; Rossi, R. (FapUNIFESP (SciELO), 2016)
The first three jets of the sperm-rich fraction of Pêga jackasses were collected and assessed separately. Five fertile Pêga jackasses were used as semen donors and underwent fractionated semen collection, using an open model artificial vagina. The first three jets of the semen were collected separately and assessed for volume, sperm motility, vigor, concentration/mL of semen, and sperm morphology. These characteristics were compared between first, second and third jets and between jackasses. It was observed that the jet volume differed (P<0.05) between jackasses, although it was similar (P>0.05) between first, second and third jets. Sperm motility did not differ (P>0.05) between jets and jackasses. Vigor was similar (P>0.05) between jets of the same jackass, and only the first jet differed (P<0.05) between jackasses. The first, second and third jets of the sperm-rich fraction had decreased sperm concentrations (P<0.05) of 955.56, 725.56 and 280.56x 106 sperm/mL of semen, respectively. Sperm morphology differed between the first three jets only for the incidence of mid-piece defect, higher in the third one (4.26%), compared to the first (3.36%) and second (3.38%) ones. When comparing the morphological characteristics of the sperm-rich fraction between five jackasses, regardless of the jet, there were differences in the percentage of normal sperm, proximal cytoplasmic droplet, mid-piece and head defects.
Keywords: Fractionated ejaculate; Jackass; Jets; Sperm-rich fraction